Waqf-Based Sustainable Education Institution Model; A Solution to Each Educational Institution Problem - Ja'far, Muhammad (Universitas Islam Negeri Imam Bonjol Padang, 2023)
Education is one of the efforts to make humans as people who have knowledge and civilized. It is known, one of these systems is a very important institution in the world, in recent years the world is facing a very dangerous outbreak that makes the economic system and education decrease, the level of educated students decreases due to the cost that makes dropping out of school by facing these events waqf becomes one of the solutions that can overcome economic problems during this pandemic, Waqf is giving an eternal substance to the community or to others to be taken advantage of.